Role of carrier number on the procoagulant activity of tissue factor in blood and plasma - Tormoen, GW (2011)
Tissue factor (TF) is a transmembrane glycoprotein cofactor of activated blood coagulation factor VII (FVIIa) that is required for haemostatic thrombin generation at sites of blood vessel injury. Membrane-associated TF, also detected in circulating blood, has been shown to contribute to experimental thrombus propagation at sites of localized vessel injury. It remains uncertain how TF can circulate without initiating intravascular coagulation. This study was designed to assess whether the carrier number per unit volume of TF-inducible monocytic cell line U937 or synthetic TF-carriers affected procoagulant activity, hence thrombogenic potential. Experiments were performed to characterize the effects of TF-carrier number on the kinetics of clot formation in both open and closed systems. The procoagulant activity of TF carriers was found to correlate with carrier count. TF carriers enhanced the amidolytic activity of FVIIa towards the chromogenic substrate, S-2366, as a function of carrier count. These results suggest that TF-initiated coagulation by circulating TF is kinetically limited by diffusion path lengths between TF-bearing surface. Biophysical parameters of circulating TF such as carrier count, and flow parameters of the circulation are therefore critical determinants of the procoagulant activity of circulating TF.